The Role of Organizational Citizenship To Increase The Influence of Transformational Leadership and School Organizational Culture on Organizational Commitment To Private High School Teachers in Pematang Siantar City - Darwin Lie; Sofiyan Sofiyan; Nana Triapnita Nainggolan; Lora Ekana Nainggolan; John Lidia (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
. The formulation of the problem of this research is how the influence of transformational leadership and school organizational culture on organizational commitment mediated by organizational citizenship behavior (OCB) on teachers SMA Swasta in Pematang Siantar. This study uses a library research and field research design. The population in this study were 420 teachers SMA Swasta in Pematang Siantar. The types of data used are qualitative data and quantitative data., and data collection techniques are carried out by questionnaires, interviews, and documentation. Then the data analysis technique uses qualitative descriptive analysis and quantitative descriptive analysis. The results of the outer loading factor test, the value of each loading factor and AVE on the variable indicators of transformational leadership, school organizational culture, organizational citizenship behavior, and organizational commitment are above 0.7 for the loading factor and above 0.5 for AVE. Furthermore, the value of each reliability obtained by the composite reliability value of each research variable is above 0.7. For Cronbach's alpha value, the value for each variable is above 0.60, meaning that all research variables have good reliability values. 6. The R-square value of the endogenous variable is 0.344 for organizational commitment, meaning that the exogenous variable explaining organizational commitment is weak. The R-square value of the endogenous organizational citizenship behavior variable is 0.155, meaning that the overall ability of exogenous variables to explain organizational citizenship behavior is weak